A CDA OF THE IDEOLOGY OF INDONESIAN TVONE NEWS REPORT - umar fauzan (JURNAL ILMIAH BAHASA DAN SASTRA, 2014)
The discourse, constructed by television as one of the mass media, is capable of directing the life of the nation through the news report program broadcasted. TVONE news report presents the same topic about the tragedy in Sidoarjo mud using their perspectives. By relying on the choice of words, the texts makers may intentionally lead public opinion to follow their understanding and “mission”. TVONE constantly uses phrases Sidoarjo mud. If one watches the same news text at TVONE over and over again, then she/he might assume that the tragedy of the mud in Sidoarjo Indonesia is a natural disaster and it has nothing to do with PT Lapindo or the Bakrie family. There is always a hidden message on any news program broadcasted by tvOne. TVONE and PT Lapindo belong to a same person, Aburizal Bakrie. He is the candidate of Indonesian president in the next presidential election. The objective of the study was to know the ideology of the news text of TVONE. This study employed a qualitative descriptive study using the model of Fairclough’s CDA. The data of the study was the news text about politics. Based on the research findings, regarding to the ideology contained in the news texts of Indonesian TVONE, then it can be concluded that TVONE does not only provide the information about the events in Indonesia, but it also develops an ideology. The ideologies are: 1) Sidoarjo mudflow is a natural disaster, 2) the cause of the mudflow is earthquake of Jogyakarta Indonesia, 3) the government and PT Lapindo are responsible for the mudflow handling and its impacts, 4) the mudflow victims got a new house and a better life, 5) the mudflow victims performs a prayer to commemorate the mudflow tragedy, and 6) Mudflow handling responsibilities have been carried out by PT Lapindo very well. The finding of this study reveals that Indonesia TVONE develops the ideology by applying the strategies: 1) Emphasize our good things and 2) De-emphasize our bad things.